Interactions among threats affect conservation management outcomes: Livestock grazing removes the benefits of fire management for small mammals in Australian tropical savannas. Issue 7 (22nd May 2019) - Legge, Sarah; Smith, James G.; James, Alex; Tuft, Katherine D.; Webb, Terry; Woinarski, John C. Z.
Abstract: Conservation scientists and practitioners usually focus on understanding and managing individual threats to biodiversity. However, threats may interact, making management outcomes unpredictable. Here, we investigated whether interactions between fire regimes and introduced livestock affect the conservation goal of population recovery for small mammals in Australia's tropical savannas, using a long‐term and landscape‐scale study. Mammal richness and abundance increased as management reduced the average annual fire extent and frequency at large and medium scales. However, these relationships between fire and richness and abundance were only evident in areas where introduced livestock were removed. This interaction may arise because predation by feral cats is amplified in areas with reduced vegetation ground cover, and cover is reduced over longer periods when livestock have access to burnt areas, because they selectively graze regenerating grass. Fire management for conservation receives substantial investment across northern Australia, and in savannas worldwide; this study shows that without appropriate management of other factors, this investment may be ineffective. More broadly, managing single threats to biodiversity may be compromised if interactions between threats are not explicitly considered. This study provides an example of how such interactions can be evaluated for improved biodiversity conservation.